Black Consciousness, Black Nationalism and Black Theology: Is there a possibility for theology of dialogue? - Resane, Kelebogile T. (HTS teologiese studies, 2021)
This article gives some historical development of Black Consciousness, Black Nationalism and Black Theology during the colonial and apartheid eras. The three worked symbiotically to address the racial injustices of the past. Each tenet is historically explained and ideologically defined. Black Consciousness and Black Nationalism are still prevalent in the South African sociopolitical landscape. This is expressed through the current political parties that are the minorities in the National Assembly. However, the ruling party, African National Congress (ANC), as a ‘broader church’ also possesses some constituents and adherents who are the Black Consciousness and Nationalistic aspirants. South Africa is developing into a peasant society regardless of capitalistic embraces of development. Poverty and equality are visible in societal structures. Those who were formerly equality aspirants are now in sociopolitical and economic circles and had forgotten their aspirations of justice and equality. Corruption, maladministration, bad governance, etc., are the menaces that cause imbalances and create a wider gap between the rich and the poor.Contribution: Black Theology is invited to lead dialogical deliberations to assess and ascertain how to bring justice into the volatile situation where people’s security and safety is uncertain and warped ideologies such as ethnic cleansing are promoted. Black Theology should resort to the theological mandate of speaking for the poor and oppressed and promote the sense of the New Testament spirit of communality.